106 Echocardiographic Evaluation Of Post-partum Ventricular Remodelling – Implications For The Detection Of Cardiac Disease. (31st May 2014) - Khan, Sitara; Melikian, Narbeh; Mushemi-Blake, Sitali; Jouhra, Fadi; Dennes, William; Monaghan, Mark; Shah, Ajay
Abstract : Background: Peripartum cardiomyopathy (PPCM) is a potentially life-threatening cause of heart failure that often presents soon after delivery. Diagnosis of the condition may be difficult due to the physiological changes in maternal cardiac function that also occur during the early postpartum period. Aims: To a) define the normal echocardiographic pattern of cardiac remodelling and changes in cardiac biomarkers in the immediate postpartum period and b) establish the overlap between normal postpartum physiology and pathological changes in PPCM. Methods: 58 healthy postpartum (PP) women (age 31.1 ± 5.6 years) and 19 healthy matched non-pregnant controls (age 31.8 ± 4.8 years) underwent an echocardiogram that included 2D strain analysis and 3D evaluation of the LV. Cardiac biomarkers were collectedin 37 women. Postpartum participants were studied within 48 h of delivery. A retrospective analysis of 12 patients diagnosed with PPCM, who had undergone 3D echocardiography at the time of diagnosis, was also performed. Data are presented as mean±SEM. Results: Compared to controls, healthy PP women had higher LV volumes, mass and sphericity index (Table 1 ). These parameters were all significantly higher in patients with PPCM (Figure 1 ). 3D ejection fraction (EF) and global longitudinal strain was reduced in healthy PP women compared to normal, the range of values overlapping with PPCM patients (Figure 2 ). Diastolic dysfunction was present in healthy PP women, as reflected by an increased E/E' lateral ratio, and a trend towards an increased E/E' septal ratio. In PPCM patients, both E/E' lateral and E/E' septal ratios were increased. Healthy PP women had higher levels of adrenomedullin, soluble fms-like tyrosine kinase-1 (sFLT-1), and high sensitivity C-reactive protein compared to controls (Table 2 ). Levels of N-terminal pro-brain natriuretic peptide were unchanged between controls and healthy PP women. sFLT-1 correlated inversely with 3D EF (r 2 = 0.13, p = 0.03). Conclusions In this first study to use 3D echocardiography for the characterisation of postpartum physiology, the LV showed geometric changes of eccentric hypertrophy, which have previously been described in pregnancy. Echocardiographic markers of systolic and diastolic function showed a small but significant impairment. There were also elevations in some serum biomarkers and there was an inverse correlation between the anti-angiogenic marker sFLT-1 and EF. Although patients with PPCM had substantially worse systolic and diastolic dysfunction than healthy postpartum women, the evidence of cardiac remodelling and changes in biomarkers in the latter group indicates that particular care is needed to confidently diagnose mild PPCM is the early postpartum period.